PENGARUH KOMPOSISI PEMEGANG SAHAM DAN STRUKTUR MODAL TERHADAP KEBIJAKAN DIVIDEN (Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2014 – 2016) - Khotimah, Rina Khusnul; Widarno, Bambang; Harimurti, Fadjar (Universitas Slamet Riyadi, 2019)
purpose ofthis research is to determine the effect of shareholder composition and capital strucutre on dividend policy.This research was conducted on manufacturing companies in the Indonesian Stock Exchange in 2014 – 2016. The population consisted of 145 companies and a sampel of 14 manufcturing campanies in the Indonesian Stock Exchange with purposive sampling technique. The independent variable in this research is dividend policy. Analysis technique using SPSS 21software. The results show that institusional share ownership variables, managerial ownershipand capital structure have a significant effect on dividend policy. Thevariables of public ownership have no significant eect on dividend policy.